Prediction of Survival and Tumor Microenvironment Infiltration Based on Pyroptosis-Related lncRNAs in Pancreatic Cancer - Xue, Shengbai; Shen, Kangjie; Wang, Kexuan; Ge, Weiyu; Mao, Tiebo; Li, Shumin; Zhang, Xiaofei; Xu, Haiyan; Wang, Yongchao; Yao, Jiayu; Yue, Ming; Ma, Jingyu; et al. (Disease Markers, 2022)
Pancreatic cancer (PC) is a fatal tumor with high mortality. Pyroptosis plays a tumor suppressor role as a novel cell death. However, the influences of the pyroptosis-related lncRNAs (PRlncRNAs) on the prognosis and tumor microenvironment (TME) infiltration have not been fully studied in PC. Using coexpression analysis and univariate Cox regression analysis, we identified seventeen prognostic PRlncRNAs from The Cancer Genome Atlas (TCGA) dataset, which were all expressed differently in normal and tumor samples. A seven-PRlncRNA risk signature was constructed and validated using the least absolute shrinkage and selection operator (LASSO) regression. Furthermore, we verified its independence and created a nomogram to validate the clinical viability of the risk signature. We then identified its relationship with clinical factors and evaluated its values in TME infiltration, functional enrichment, tumor mutation, and therapeutic responses in PC. Lower ImmuneScore, ESTIMATEScore, and advanced tumor stage were connected with high-risk score. The low-risk group was characterized by better OS, elevated immune activation, and higher susceptibility of pazopanib and sunitinib. The high-risk group possessed a worse immune infiltration and poor survival, with higher tumor mutations and lapatinib and paclitaxel that may be better choices in this group. In conclusion, we developed an original seven-PRlncRNA risk signature to predict prognosis, TME infiltration, tumor mutation, and therapeutic options for PC patients.